Comparison of the rates of emergent otologic adverse events following mRNA COVID-19 versus influenza vaccination: a matched cohort analysis - Munjal, Tina; Batts, Shelley; Gombar, Saurabh; Stankovic, Konstantina M. (Frontiers in Neurology, 2025)
BackgroundOtologic adverse events (AEs) have been occasionally reported as sequalae of COVID-19 vaccination, although their incidence in comparison with that of preexisting vaccines with high uptake remains unclear. This study compared the rates of new-onset otologic AEs among matched adults receiving mRNA COVID-19 vaccination versus influenza vaccination.MethodsThis retrospective cohort study used electronic health records (EHR) data from Stanford Health Care to identify adults aged 50–89 years with no history of otologic disorders prior to first Pfizer/Moderna COVID-19 vaccine (December 2020–January 2022) or any pre-pandemic influenza vaccine (January 2016–December 2019). Patients were categorized by vaccination into FluVax or COVIDVax cohorts. A 90-day history pre-vaccination (baseline period) and ≥6 months follow-up post-vaccination were required. Event rates of new-onset hearing loss (HL), sudden HL, tinnitus, vertigo/dizziness, aural fullness, and otalgia in the 6 months post-vaccination were compared between groups after high-dimensional propensity score (hdPS) matching. A sensitivity analysis was conducted among patients with no COVID-19 infection at any time. Odds ratios (ORs) were calculated using logistic regression for the hdPS matched cohorts.ResultsAfter hdPS matching, 20,325 patients were included into the FluVax and COVIDVax cohorts, respectively (mean age: 65.5 and 65.2 years; 53.1 and 53.8% females). The rates of otologic AEs in the 6 months post-vaccination were similarly low for the FluVax and COVIDVax cohorts: 1.16% vs. 1.16% for any HL, 0.01% vs. 0.02% for sudden HL, 0.41% vs. 0.47% for tinnitus, 1.96% vs. 1.59% for vertigo, 0.27% vs. 0.25% for otalgia, and 0.09% vs. 0.2% for aural fullness. COVIDVax patients had lower odds of vertigo [OR 95% CI: 0.81 (0.70, 0.94)] and higher odds of aural fullness [2.16 (1.25–3.72)] than the FluVax patients (both p < 0.05). The results of the sensitivity analysis limited to patients with no COVID-19 infection at any time (N = 17,530 each cohort) were consistent with the primary results, but aural fullness was the only AE with statistically higher risk in the COVIDVax vs. FluVax cohort [OR (95% CI): 1.90 (1.09–3.31); p = 0.021].ConclusionNew-onset otologic AEs were rare among a large cohort of hdPS-matched patients who received mRNA COVID-19 or pre-pandemic flu vaccination at a single institution. Although aural fullness was statistically more common in the COVIDVax vs. FluVax cohort, regardless of COVID-19 infection status, it remained extremely rare (<0.22%) in any cohort. These results indicate a similar otologic safety profile of the two vaccines, although future research is recommended in larger EHR databases to corroborate the findings.